Fabrication of sliver nanoparticles/polyvinyl alcohol/gelatin ternary nanofiber mats for wound healing application. (August 2020) - Amer, Somaya; Attia, Noha; Nouh, Samir; El-Kammar, Mahmoud; Korittum, Ahmed; Abu-Ahmed, Howaida
Purpose: In this study, we aimed to determine the regenerative and antimicrobial impact of the electrospun nanofiber mats, with/without silver nanoparticles (AgNPs), on full-thickness skin wounds in rabbits. Methods: Polyvinyl alcohol was combined with gelatin to provide biocompatible electrospun binary nanofiber mats. AgNPs were added to the polyvinyl alcohol/gelatin mixture to obtain ternary nanofiber-AgNPs mats. Binary and ternary nanofiber mats were characterized by scanning electron microscopy before being applied as wound dressings in vivo. Subsequently, wound healing was evaluated. Results: Both nanofiber/nanofiber-AgNPs mats improved the microscopic quality of the healed skin, albeit without obvious acceleration of the healing rate. As well, both types of nanofiber mats were able to combat microbial invasion into the wound bed. Conclusions: Both binary polyvinyl alcohol/gelatin and ternary polyvinyl alcohol/gelatin/AgNPs nanofiber mats developed in the present study depicted similar regenerative and antimicrobial potential when applied as full-thickness wound dressing. However, in comparison to the binary nanofiber mats, no obvious synergistic effect was observed after loading nanofibers with AgNPs.